2018
DOI: 10.1016/j.micpath.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei 28.4 reduces in vitro hyphae formation of Candida albicans and prevents the filamentation in an experimental model of Caenorhabditis elegans

Abstract: The objective of this study was to evaluate the influence of microbe-microbe interactions to identify a strain of Lactobacillus that could reduce the filamentation of Candida albicans ATCC 18804 using in vitro and in vivo models. Thus presenting a probiotic effect against the fungal pathogen. First, we analyzed the ability of 25 clinical isolates of Lactobacillus to reduce filamentation in C. albicans in vitro. We found that L. paracasei isolate 28.4 exhibited the greatest reduction of C. albicans hyphae (p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 69 publications
1
38
0
Order By: Relevance
“…We have shown that even after curative treatment with the LBM, the digestive tract of the nematode is colonized by the pathogen without showing a pathological state. These data are in accordance with De Barros et al and suggest that Lcr35 ® induced repression of virulence factors in C. albicans [16]. In C. elegans, DAF-16 is closely related to mammalian FOXO3a, a transcription factor involved in the inflammatory process [38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have shown that even after curative treatment with the LBM, the digestive tract of the nematode is colonized by the pathogen without showing a pathological state. These data are in accordance with De Barros et al and suggest that Lcr35 ® induced repression of virulence factors in C. albicans [16]. In C. elegans, DAF-16 is closely related to mammalian FOXO3a, a transcription factor involved in the inflammatory process [38].…”
Section: Discussionsupporting
confidence: 91%
“…These have provided answers about the mechanisms of action allowing an LBM to prevent the installation of a pathogen with, for instance, the reduction of C. albicans hyphae formation [12][13][14][15][16]. However, few studies showing the efficacy of LBM against candidiasis have been conducted and no "curative" study relative to C. albicans was conducted using the nematode C. elegans [12,16]. The only curative study was carried out by Sharma and colleagues against infections with E. coli pathogenic strains [17].…”
Section: Introductionmentioning
confidence: 99%
“…ere is also some published literature on the use of models to simulate wound healing [130,131], but there is still no published literature on the use of probiotics with them. Another possibility is the use of the nematode's Caenorhabditis elegans epidermis as a model skin [132,133]. ere is even an international patent for microspheres from gelatin as a carrier for probiotic Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, outside of the host environment, lactic acid could be less important as antifungal agent. In a co-culture system with C. albicans, L. paracasei [120] and L. rhamnosus, L. casei and L. acidophilus [13] do not acidify the environment significantly. This could indicate that these isolates do not produce sufficient amount of lactic acid.…”
Section: Lactic Acidmentioning
confidence: 95%
“…These differences could arise from the media used for co-culture. Whereas both studies used brain heart infusion (BHI) broth for their assays [13,120], we used MRS, which favors Lactobacillus growth and is slightly acidic. Of note, BHI medium is buffered to a neutral pH.…”
Section: Lactic Acidmentioning
confidence: 99%